Plumbago indica L. Root Extract Induces Anti-proliferation, Anti-migration and Apoptosis on the Human Lung Cancer Cell Line - Phiphitphibunsuk, Wichuda; Buranrat, Benjaporn (Indian Journal of Pharmaceutical Education and Research, 2024)
Background Plumbago indica L. (PI) is a Thai traditional medicine that has been reported to improve health benefit including anticancer property. Nevertheless, the effects of PI and this mechanism are still less data in lung cancer. Aim To investigate and compare the effects of PI root extract with high and low active compound, plumbagin, on the growth inhibition and apoptotic induction in A549 lung cancer cells with underlying mechanism. Materials and Methods Antiproliferative effects of PI were examined by Sulforhodamine B (SRB) and colony formation method. Migratory suppression was studied by Wound healing and Matrigel migration assay. Apoptotic induction, ROS formation, and mitochondrial function were explored by flow cytometric method. Western blotting was used to measure the protein expression. Results PI extract with high plumbagin level reduced cell viability by dose- and time-dependent than low plumbagin extract and the data was correlated with colony formation assay. Further, the results of migration assay indicated that 50 μg/mL of high plumbagin also caused induction of anti-migratory effects than low plumbagin. For apoptosis, both of PI extract activated the late apoptosis, especially at high dose of PI extract (50 μg/mL) along with stimulation of ROS formation and mitochondrial dysfunction. The mechanism of apoptosis was observed through the induction of expression of active-caspase 3 level correlated with reduction of pro-caspase 3 expression. Conclusion Therefore, these anti-cancer activities of the PI extract with high plumbagin could be served as the potential beneficial effects on lung cancer than low plumbagin. Additionally, the study of PI effects in vivo study is now required to support this in vitro study information.
Keywords: Plumbago indica (PI); Apoptosis; Anti-proliferation; Human lung cancer cell line; Migration; Mitochondrial function